2017
DOI: 10.1186/s12884-017-1451-0
|View full text |Cite
|
Sign up to set email alerts
|

Signal functions for emergency obstetric care as an intervention for reducing maternal mortality: a survey of public and private health facilities in Lusaka District, Zambia

Abstract: BackgroundZambia’s maternal mortality ratio was estimated at 398/100,000 live births in 2014. Successful aversion of deaths is dependent on availability and usability of signal functions for emergency obstetric and neonatal care. Evidence of availability, usability and quality of signal functions in urban settings in Zambia is minimal as previous research has evaluated their distribution in rural settings. This survey evaluated the availability and usability of signal functions in private and public health fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
34
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 14 publications
(7 reference statements)
4
34
1
Order By: Relevance
“…Health service factors also influence the rates of PPH including, physical resources (characteristics of the hospital, equipment and supplies) and human resources (health care providers). There is evidence that hospitals with number of deliveries < 200 cases per year had higher odds of PPH than in high-volume delivery hospitals [15] and that some hospitals could not provide emergency obstetric care (EmOC) as they lacked equipment and supplies [16,17]. Moreover, it has been shown that a larger number of patients to nurse ratio, increased the incidence of patients adverse health outcomes [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Health service factors also influence the rates of PPH including, physical resources (characteristics of the hospital, equipment and supplies) and human resources (health care providers). There is evidence that hospitals with number of deliveries < 200 cases per year had higher odds of PPH than in high-volume delivery hospitals [15] and that some hospitals could not provide emergency obstetric care (EmOC) as they lacked equipment and supplies [16,17]. Moreover, it has been shown that a larger number of patients to nurse ratio, increased the incidence of patients adverse health outcomes [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Of the 15 studies, seven were assessed to be of high quality [8,9,16-20], 4 were medium quality [21-24] and the remaining 4 studies were assessed as being of low quality [25-28] (See Quality assessment of studies in Appendix S2 in Online Supplementary Document ).…”
Section: Resultsmentioning
confidence: 99%
“…The peak publication year was in 2011 [8,22,24,25] and 2016 [16,17,21,27] when 4 articles were published in each year ( Figure 2 ). 2 studies have each been published in Burkina-Faso [26,27], Ethiopia [8,25], Ghana [17,19], Tanzania [20,21] and Zambia [22,28]. Guinea [16], Kenya [18], Malawi [23], Sierra-Leone [24], Rwanda [9] each have 1 published study ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations